Pengaruh Luas Lahan, Modal, Dan Tenaga Kerja Terhadap Pendapatan Petani Cabai Di Kecamatan Labuhan Haji - Imran, Ali; Utomo, Danang Prio (Alpatih Harapan Semesta, 2023)
This study aims to determine the area of ​​land, capital, and labor partially or simultaneously affect the income of chili farmers in Labuhan Haji District, East Lombok Regency. The method used is a quantitative method with a descriptive approach. The subjects of this study were 99 chili farmers in Labuhan Haji District, East Lombok Regency. The data collection techniques and instruments used in this study were by conducting observations and using questionnaires. The data from this study were then analyzed using the classical assumption test, namely the normality test, multicollinearity test, and heteroscedasticity test. The results of this study indicate; 1) land area, capital, and labor partially affect the income of chili farmers in Labuhan Haji District, East Lombok Regency. This is indicated by the results of land area to income with a calculated t value > t table (5.863 > 1.985), capital to income with a calculated t value > t table (4.702 > 1.985), labor to income with a calculated t value > t table (4.055 > 1.985). 2) land area, capital, and labor simultaneously affect the income of chili farmers in Labuhan Haji District, East Lombok Regency, this is indicated by f count > f table (38.086 > 2.70).